2006
DOI: 10.1007/s10350-006-0549-7
|View full text |Cite
|
Sign up to set email alerts
|

Anal Manometry: A Comparison of Techniques

Abstract: There is no significant variation in anal pressure recordings using standard manometry techniques. Variations in radial pressures are slight and not significant in clinical studies. Results obtained with portable nonperfusion systems must be interpreted appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Briefly, all patients were aged between 18 and 75 years, and had scintigraphically confirmed slow transit constipation . All patients had undergone anorectal function studies and had no evidence of paradoxical sphincter contraction nor an inability to expel a rectal balloon …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, all patients were aged between 18 and 75 years, and had scintigraphically confirmed slow transit constipation . All patients had undergone anorectal function studies and had no evidence of paradoxical sphincter contraction nor an inability to expel a rectal balloon …”
Section: Methodsmentioning
confidence: 99%
“…A complete bowel movement was defined as expulsion of stool following which the individual felt that evacuation was complete 20 . These data were derived from 3‐week stool diaries that detailed, on a daily basis, stool frequency and form, 21 and sense of complete evacuation (yes/no); (iv) delayed colonic transit confirmed by isotope colonic transit study; 22,23 (v) normal anorectal manometry, with no evidence of strain‐related paradoxical sphincter contraction or an inability to expel a rectal balloon; 24 (vi) normal evacuation proctogram, with no functional (e.g. pelvic floor dyssynergia) or anatomical (e.g.…”
mentioning
confidence: 99%
“…12 Brown et al, 2 in 1990, studied 99 healthy young volunteers and reported that 29 percent of them claimed that coffee induced a desire to defecate, therefore, they were called coffee-responders. Multiport manometry in 14 of these volunteers revealed an increase in the rectosigmoid motility index within 4 minutes, which lasted at least 30 minutes, after ingestion of both regular and decaffeinated coffee, in eight responders but not in the six nonresponders.…”
Section: Discussionmentioning
confidence: 97%